An integrated modelling methodology for estimating the prevalence of centronuclear myopathy - Vandersmissen, I; Biancalana, V; Servais, L; Dowling, JJ; Stichele, GV; Van Rooijen, S; Thielemans, L (Elsevier, 2018)
Centronuclear myopathies (CNM) are a group of rare inherited muscular disorders leading to a significantly reduced quality of life and lifespan. To date, CNM epidemiologic reports provide limited incidence and prevalence data. Here, an integrated model utilizing available literature is proposed to obtain a better estimate of overall CNM patient numbers by age, causative gene, severity and geographic region. This model combines published epidemiology data and extrapolates limited data over CNM subtypes, resulting in patient numbers related to age and disease subtype. Further, the model calculates a CNM incidence twofold the current estimates. The estimated incidence of 17 per million births for severe X-linked myotubular myopathy (XLMTM), the main subtype of CNM, corresponds to an estimated prevalence of 2715 in the US, 1204 in the EU, 688 in Japan and 72 in Australia. In conclusion, the model provides an estimate of the CNM incidence, prevalence and survival, and indicates that the current estimates do not fully capture the true incidence and prevalence. With rapid advances in genetic therapies, robust epidemiologic data are needed to further quantify the reliability of incidence, prevalence and survival rates for the different CNM subtypes.